If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying F + -2 = 3f + 6 Reorder the terms: -2 + F = 3f + 6 Reorder the terms: -2 + F = 6 + 3f Solving -2 + F = 6 + 3f Solving for variable 'F'. Move all terms containing F to the left, all other terms to the right. Add '2' to each side of the equation. -2 + 2 + F = 6 + 2 + 3f Combine like terms: -2 + 2 = 0 0 + F = 6 + 2 + 3f F = 6 + 2 + 3f Combine like terms: 6 + 2 = 8 F = 8 + 3f Simplifying F = 8 + 3f
| 5(x+3)+3(x-1)=-9 | | X/4+7=14 | | 21=(5x/6)+(3x/2) | | 2(x-4)+3(x+5)=2x | | 5.3q-1.9-4.6q=-0.3q-1.5 | | 2x-8+3x+18=2x | | 33/25*10/117*27/22 | | -2y+5x=-9 | | 62-9x=7x+18 | | x/3-26 | | 2x-5=57 | | x/2=48 | | x/4+x/3=7/4 | | 2f-7=43 | | x/6=15 | | x/2=46 | | 5c-11=19 | | 4x+14=112-10x | | 4x^2+3x-7=2x-2 | | 9-5p= | | 3b+7=52 | | 10r-12=-28 | | f=(g-h+k)/5 | | y=-2/2+2 | | F(x)=4x^2-x-3 | | 22x-18=36+16x | | 2m+15=-23 | | -3y-5=-2 | | 8(x+6)+5=8x+5 | | x-7.1=5.4 | | 4x-9=6-13 | | z+37=14 |